Anti-Leptospira spp. antibodies in captive animals in Paraíba State - Brasil, Arthur; Parentoni, Roberta; Farias, Roberto; Nery, Thiago; Vasconcellos, Sílvio; Azevedo, Sérgio Santos de (Semina: Ciências Agrárias, 2013)
The aim of this survey was to verify the occurrence of anti-Leptospira spp. antibodies in captive animals in the Parque Zoobotânico Arruda Câmara, João Pessoa, Paraíba State, Northeastern Brazil. Blood samples were collected from 49 animals: 26 mammals of the species Sapajus libidinosus, Cebus flavius, Saimiri sciureu, Coendu sp., Pseudalopex vetulus, Leopardus pardalis, Leopardus tigrinus, Galactitis vitata, Eira barbara, Nasua nasua, Tayassu tajacu and Ratus norvegicus; 10 birds of the species Penelope jacucaca, Pavo cristatus, Anodorhynchus hyacinthinus, Ara chlorothpterus, Pionites leucogaster, Polyborus plancus, Geranoaetus melanoleucus and Urubitinga urubitinga; and 13 reptiles of the species Caiman latirostris, Paleosuchus trigonatus, Caiman crocodilus, Tupinabis merinae, Tupinambis teguixin, Boa constrictor, Corallus hortulanus, Python molurus, Bufocephala vanderhaegei, Geochelone denticulata and Geochelone carboraria. Sera were examined by the microscopic agglutination teste (MAT) using 24 serovars as antigens and cut-off point of 1:100. One ocelot (Leopardo pardalis) presented positive reaction for the Icterohaemorrhagiae serovar with titer of 100, however, it did not show any clinical sign of the infection. Sinantropic rodents are the main reservoirs of this serovar, which suggests the need of maintenance and continuous evaluation of rodent control programs.